2007
DOI: 10.1111/j.1469-8749.2005.tb01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanical alterations in spastic skeletal muscle

Abstract: Spasticity, a neurological problem secondary to an upper motor neuron lesion, has a significant effect on skeletal muscle. The upper motor neuron lesions may be secondary to a cerebral vascular accident, head injury, spinal cord injury, or degenerative diseases such as multiple sclerosis, or perinatal brain injuries such as cerebral palsy. Functional ability in these patients can be severely compromised but the basic mechanisms underlying these deficits are not clearly understood. In this review we evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…One of the most frequently used definitions of spasticity defines it as ''a motor disorder characterized by a velocity-dependent increase in tonic stretch reflexes with exaggerated tendon jerks, resulting from hyper-excitability of the stretch reflex'' (Lance, 1980), and spasticity is typically measured as resistance to passive movement. However, it is generally accepted that the resistance felt during passive muscle stretch includes both passive and active muscular components that are changed in a spastic muscle (Foran et al, 2005). This makes it challenging to differentiate between what is ''true'' spasticity and what might be structural changes, by studying resistance only.…”
Section: Introductionmentioning
confidence: 96%
“…One of the most frequently used definitions of spasticity defines it as ''a motor disorder characterized by a velocity-dependent increase in tonic stretch reflexes with exaggerated tendon jerks, resulting from hyper-excitability of the stretch reflex'' (Lance, 1980), and spasticity is typically measured as resistance to passive movement. However, it is generally accepted that the resistance felt during passive muscle stretch includes both passive and active muscular components that are changed in a spastic muscle (Foran et al, 2005). This makes it challenging to differentiate between what is ''true'' spasticity and what might be structural changes, by studying resistance only.…”
Section: Introductionmentioning
confidence: 96%
“…Although not fully elucidated, emerging evidence suggests that contracture formation is a highly multifactorial process, with neural and muscular factors (Barrett and Lichtwark, 2010), as well as endocrinal, nutritional and mechanical influences all proposed to play a significant role (Gough and Shortland, 2012). The presumption that contractures are due to reduced muscle fibre length and number of in-series sarcomeres has been challenged (Foran et al, 2005), with inconsistent findings in the few studies that have directly evaluated fibre length in individuals with spastic CP (Barrett and Lichtwark, 2010). While Mohagheghi et al (2008) found significant shortening of fascicle length in the gastrocnemius of children with diplegic CP, several others did not (Shortland et al, 2002;Malaiya et al, 2007;Barber et al, 2011), suggesting that atrophy and shortening may result from a reduction in muscle fibre diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, composition of ECM is changed and has an elasticity modulus which is only 1/40 that of the ECM in unaffected musculature. For these reasons, spasticity affects not only active movements but also results in inferior mechanical properties [4,6,11,12].…”
Section: Discussionmentioning
confidence: 99%